Screening for burn-out in Australian medical students undertaking a rural clinical placement - Vivian Isaac; Craig S McLachlan; Lucie Walters; Jennene Greenhill (BMJ Open)
Objective To investigate Australian medical student burn-out during rural clinical placement. Second, to examine the association between perceived burn-out and rural career intent at the time of finishing their rural placement.Design, settings and participants The 2016 Federation of Rural Australian Medical Educators evaluation survey is a cross-sectional study of medical students from 17 Australian universities. Specifically, those medical students who completed a full academic year or more at a Rural Clinical School (RCS). Responses from 638 medical students from regional Australia were analysed in the study of all eligible 756 medical students (response rate 84.3%).Primary and secondary outcome measures The primary objective was to determine self-reported burn-out (emotional exhaustion) in rural placements for medical students. Secondary outcome measures were designed to explore interactions with rural practice self-efficacy and rural intentions. Logistic regression models explored factors associated with burn-out.Results 26.5% of students reported experiencing burn-out during a rural placement. Factors associated with burn-out were female gender, rural origin, low preference for RCS, stress in the year prior to a rural clinical placement, perceived social isolation during rural placement and lower rural practice self-efficacy. Burn-out was not associated with rural career intentions. Social isolation and low rural self-efficacy were independently associated with burn-out during rural placement and together explained 10% of variance in burn-out (Model Nagelkerke R2=0.23).Conclusion Burn-out during rural placement may be a consequence of stress prior to a medical school placement. Social isolation and rural self-efficacy are amendable factors to mitigate medical student burn-out during rural placements.